The Effect of Pictures as Media to Improve Students’ English-Speaking Ability - Putri, Alfira (Institut Agama Islam Negeri Ponorogo, 2023)
The background of this study was that many students mispronounce grammar and lack confident to speak English of students in tenth grade, who were slow in understanding how to speak English with the correct pronounce and the teacher did not media in learning English. This study aimed to determine the effectiveness of picture as media to improve students’ English-speaking ability at tenth-grade of SMA Muhammadiyah Pangkalpinang. This study used quantitative research with a quasi-experimental design method with non-equivalent control group design. The population in this study were students of tenth grade SMA Muhammadiyah Pangkalpinang, with a total 54 students. The sample in this study was 18 students for the experimental group and 18 students for the control group. data collection techniques in this study were some tests. The data analysis technique used the normality test, homogeneity test, and hypothesis. The result of this study that indicated the hypothesis test result between the experiment and control class have T count = 3.767 > T table = 2.032, it showed that H0 was rejected and Ha was accepted. This research showed that there was an effectiveness of picture as media to improve students’ English-speaking ability at tenth-grade of SMA Muhammadiyah Pangkalpinang.